ANALISIS PROMOSI JABATAN PEGAWAI BADAN KEPEGAWAIAN DAERAH DI KOTA MEDAN* - Reza Khairina (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
This research aims at analyzing procedures, processes and constraints concerning personnel promotion at Medan City Civil Service Office. It also tries to identify efforts done to overcome the constraints. It is a descriptive, qualitative research. Data are gathered through observation, interviews and literature study. Data processing is conducted through reduction, arrangement andtriangulation. The result shows that the implementation of personnel promotion at Medan City Civil Service Office is yet to be in accordance with performance-based promotion system. Therefore, the writer recommends that: (a) Job information at Medan City Civil Service Office should be open and accessible; (b) Baperjakat (Rank and Post Consideration Board) provides fair evaluation for all structural official candidates, not only for echelon II structural posts; dan (c) Proposals ofstructural official candidates by users (direct senior officers) should be based on job requirements and performance-based system.